Efektywność gospodarowania w leśnictwie – przegląd literatury - Młynarski, Wojciech; Kaliszewski, Adam (Leśne Prace Badawcze, 2018)
The aim of our work was to give an overview on efficiency evaluation in forest management as described in the literature. Here we present definitions for efficiency and productivity of economic entities as well as categories of efficiency evaluation methods and discuss ratio analysis, parametric and non-parametric approaches to measure efficiency in forestry. With regards to ratio analysis, we focused on reports employing this approach in Poland due to the abundant literature on this subject. On the other hand, studies based on parametric and non-parametric approaches for efficiency evaluation in the forest sector have only been used occasionally in Poland and thus this part of our analysis is based on research done abroad. The most important parametric method is the Stochastic Frontier Approach (SFA), while the most important non-parametric approach involves Data Envelopment Analysis (DEA), which was developed at the end of the 1970s and utilizes a mathematical programming algorithm. Our review shows that efficiency evaluation in forest management in Poland so far is mostly based on ratio analysis. However, although those methods are of considerable practical importance, in terms of scientific development they are now being replaced by more mathematically and statistically advanced parametric and non-parametric methods, which also open up more opportunities to analyze the efficiency of forest management. The first research employing non-parametric DEA recently published in Poland is a good step towards improving research quality and provides comprehensive results for the efficiency evaluation of forest management.